On landscape and its function in the works of Luis Mateo Díez, Julio Llamazares and Jesús Moncada. Brief notes - Acín, Ramón (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paprt studies the role of landscape in the narrative work of Luis Mateo Díez, Julio Llamazares and Jesús Moncada, especially in its relationship with memory in front of the passage of time and the threat of ruin, disappearance and oblivion that it entails.